Considerations on the General Law to Prevent and Punish Kidnapping Crimes in Mexico: A Critical Analysis of its Foundations - Escutia-Paredes, Laura (2022)
This article analyzes and reflects on the meaning of the General Law to Prevent and Punish Kidnapping Crimes in Mexico. The objective is to analyze the possibility of measuring the progress and steps taken in the incorporation of fundamental rights, in the construction of the country's democracy, in the design of the criminal policy of kidnapping and the extension of constitutional guarantees to all people, including those who have violated the law. From the methodological perspective, this research is composed of a theoretical-reflective element that, for its development, took into consideration the classical theories of contractualism on the State, the neo-constitutionalist perspective, the exercise of guarantees and fundamental rights of citizenship, as well as the existence of security, since it does not necessarily mean the validity of the rule of law. In addition, a critical analysis of the law that was implemented from 2010 to mitigate the crime of kidnapping is carried out. It is concluded that the penalties imposed for kidnapping affect the rights of the accused persons, which is obvious with the tightening of the penal system.